2022
DOI: 10.1021/acsaem.2c00485
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Irradiation-Induced Defects for Enhancing Thermoelectric Properties of Scandium Nitride Thin Films

Abstract: Scandium nitride (ScN) is an emerging rocksalt indirect bandgap semiconductor with the potential to overcome some of the limitations of traditional wurtzite III (A)-nitride semiconductors in next-generation optoelectronic and thermoelectric applications. Epitaxial ScN thin films contain point defects such as oxygen impurities that result in a high carrier concentration and help achieve a high thermoelectric power factor. However, due to its high thermal conductivity, the thermoelectric figure-of-merit (zT) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The large decrease of thermal conductivity in implanted ScN thin films either with noble gas (Ar in this study, see Table 2 ), with dopants (Mg in a previous study), or by nonelectrically active element (Li + ) may be explained by the as-introduced defects, which reduce the mean phonons free path, increasing thus the level of scattering. 18 , 19 The increase of thermal conductivity occurring during the subsequent high-temperature annealing suggests a partial recovery of defects. However, the Seebeck curves and electrical characterizations provide a more complete picture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The large decrease of thermal conductivity in implanted ScN thin films either with noble gas (Ar in this study, see Table 2 ), with dopants (Mg in a previous study), or by nonelectrically active element (Li + ) may be explained by the as-introduced defects, which reduce the mean phonons free path, increasing thus the level of scattering. 18 , 19 The increase of thermal conductivity occurring during the subsequent high-temperature annealing suggests a partial recovery of defects. However, the Seebeck curves and electrical characterizations provide a more complete picture.…”
Section: Discussionmentioning
confidence: 99%
“… 17 More recently, it has been shown that defect introduction using Mg-dopant implantation leads to an increase in the Seebeck coefficient coupled with a drop in the thermal conductivity k total , down to 3.2 W m –1 K –1 for the ScN sample implanted with 2.2 atom % of Mg. 18 Another study has shown the potential of Li + -implanted ScN for which the thermal conductivity is divided by half in the 300–700 K temperature range. 19 Defect engineering by ion implantation and other techniques has shown potential for improvement of thermoelectric properties. However, the control of the induced defect in a material is always a challenge in terms of their formation during irradiation/implantation, the type of defect, and their stability with temperature, which is critical for thermoelectric applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical calculations showed that scandium and nitrogen vacancies in ScN introduce asymmetric states close to the Fermi energy, increasing its Seebeck coefficient. 95 Bivas et al irradiated molecular beam epitaxy-deposited ScN thin films with 35 keV Li + ions 96 and found that the irradiated ScN films showed a significant increase in the Seebeck coefficient. Thermal conductivity decreases by more than half to 7 ± 1 W m −1 K −1 at room temperature due to phonon scattering by the irradiation-induced defects.…”
Section: Ion Beam Modification Of Energy Materialsmentioning
confidence: 99%
“…The improvement of ZT values has been one of the major challenges in the field in recent years and has been tackled largely by controlling the dimensions of materials on the nanoscale. A nanostructured material has a lower thermal conductivity than the corresponding bulk material because it exhibits more phonon scattering and deformation of its density of states, which results in its thermoelectric power [ 6 ]. Metal chalcogenide materials, such as SnSe, PbTe, CoSb, and BiTe, have been more effectively used for thermoelectric applications than other equivalent oxide materials because the electronegativity difference between these pairs of elements is low.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the creation of point defects and vacancies on irradiation act as carrier traps that could be the reason for the decrease in mobility. Additionally, heavy ion beam irradiation proposes an important means of alloy formation with the creation of defects and nanostructures in the material, which eventually lead to enhanced thermopower and the lowering of the thermal conductivity by carrier energy filtering and phonon scattering, respectively [ 6 , 10 , 19 ]. SHI passes through the target and predominantly deposits large energy in the electronic sub-system of the material, creating point defects that can be electrically active and enhance the charge transport in the lattice [ 10 ].…”
Section: Introductionmentioning
confidence: 99%